2016
DOI: 10.1002/ece3.2298
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in putative male sex pheromone components across and within populations of the African butterfly Bicyclus anynana as a potential driver of reproductive isolation

Abstract: Sexual traits are often the most divergent characters among closely related species, suggesting an important role of sexual traits in speciation. However, to prove this, we need to show that sexual trait differences accumulate before or during the speciation process, rather than being a consequence of it. Here, we contrast patterns of divergence among putative male sex pheromone (pMSP) composition and the genetic structure inferred from variation in the mitochondrial cytochrome oxidase 1 and nuclear CAD loci i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 99 publications
(174 reference statements)
0
13
0
Order By: Relevance
“…While traditionally predicted to be under stabilizing selection, intraspecific variation between populations in chemical profiles has been documented in other Lepidoptera (Carde & Allison, 2016). Chemical divergence in putative male sex pheromones between populations of Bicyclus anynana is reported to be as large as differences between Bicyclus species and is greater than predicted by genetic divergence (Bacquet et al, 2016). This is in contrast to what we find here, where interspecific differences are much greater than intraspecific ones.…”
Section: Discussionmentioning
confidence: 99%
“…While traditionally predicted to be under stabilizing selection, intraspecific variation between populations in chemical profiles has been documented in other Lepidoptera (Carde & Allison, 2016). Chemical divergence in putative male sex pheromones between populations of Bicyclus anynana is reported to be as large as differences between Bicyclus species and is greater than predicted by genetic divergence (Bacquet et al, 2016). This is in contrast to what we find here, where interspecific differences are much greater than intraspecific ones.…”
Section: Discussionmentioning
confidence: 99%
“…However, the learning process that we describe here, by allowing males with divergent blends to reproduce, may mitigate the strength of stabilizing selection, and create opportunities for pheromone blends and reception systems to evolve. A recent study suggested that quantitative and qualitative variations observed in blends within and between natural B. anynana populations are potentially catalyzing ongoing speciation (6). The odor learning ability of B. anynana females has probably maintained the high variance in MSP amounts measured in different stock populations (24, 25, 30), as 225 well as the variance in MSPs detected across natural populations (6).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that quantitative and qualitative variations observed in blends within and between natural B. anynana populations are potentially catalyzing ongoing speciation (6). The odor learning ability of B. anynana females has probably maintained the high variance in MSP amounts measured in different stock populations (24, 25, 30), as 225 well as the variance in MSPs detected across natural populations (6). Furthermore, the use of multimodal signals in mate selection in B. anynana , where females use both olfactory and visual signals to assess mate quality (11, 23, 28), may facilitate pheromone learning and the evolution of the MSP blends.…”
Section: Discussionmentioning
confidence: 99%
“…However, the learning process that we describe here, by allowing males with divergent blends to reproduce, may mitigate the strength of stabilizing selection, and create opportunities for pheromone blends and reception systems to evolve. A recent study suggested that quantitative and qualitative variations observed in blends within and between natural B. anynana populations are potentially catalyzing ongoing speciation 6 . The odor learning ability of B. anynana females has probably maintained the high variance in MSP amounts measured in different stock populations 28,30,33 , as well as the variance in MSPs detected across natural populations 6 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that quantitative and qualitative variations observed in blends within and between natural B. anynana populations are potentially catalyzing ongoing speciation 6 . The odor learning ability of B. anynana females has probably maintained the high variance in MSP amounts measured in different stock populations 28,30,33 , as well as the variance in MSPs detected across natural populations 6 . Furthermore, the use of multimodal signals in mate selection in B. anynana , where females use both olfactory and visual cues to assess mate quality 12,26,27 , may facilitate pheromone learning and the evolution of the MSP blends.…”
Section: Discussionmentioning
confidence: 99%